Penyuluhan Kesehatan Pemanfaatan Tanaman Berkhasiat Obat Di Desa Kedungsari Kecamatan Klirong Kabupaten Kebumen - Handayani, Eka Wuri; Yuniarti, Endang; Fatonah, Sri; Agustna, Navi (Prosiding University Research Colloquium, 2022)
Indonesia is a country rich in biodiversity and has great opportunities for the development of herbal medicine research. It has been empirically proven and from generation to generation the use of efficacious plants as herbal medicine and traditional medicine. Traditional medicine has also received support from BPOM which is committed to supporting the use of Indonesian herbs and traditional medicines to be developed into herbal medicinal products, traditional medicines as health supplements for the prevention of the Covid-19 virus. The purpose of this community service is to help increase public awareness in the use of medicinal plants to improve the body's immune system based on the plant parts used, processing methods, sources, and uses and to help find TOGA land to be used by the people of Kedungsari Village as a step to prevent the Covid-19 virus. 19. The results of the extension activities of medicinal plants based on the results of the questionnaire obtained that the level of knowledge of PKK mothers in Kedungsari village, Klirong district was good, seen from the pre-test results with an average of 81.5 and post-test results of 92.5. From these data it can be concluded that sosialization can increase public understanding of TOGA in Kedungsari Village, Klirong District, Kebumen Regency.